2022
DOI: 10.1039/d2cp04102b
|View full text |Cite
|
Sign up to set email alerts
|

Facilely synthesized carbon dots and configurated light-emitting diodes with efficient electroluminescence

Abstract: Carbon dots (CDs) are recently emerged photoluminescence (PL) and electroluminescence (EL) emitters and highly spotlighted in solid-sate lighting. Herein, exceptional CDs with fewer defects, high carbonation, good film morphology and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Different from powder processing and vacuum evaporation, in which vapor is transported to a substrate to form thin films, due to its simple operation process and low cost, spin-coating is compatible with widely available nanosized CDs that are easily carbonized at high temperatures. [160,161] However, during film processing, the film morphology and microstructure are completely different under different conditions, especially considering that CDs experience molecular rearrangement, aggregation and assembly that are quite different from the dispersed monomolecular structure in solution states. The commonly used processing techniques are still immature for CD materials whose optical properties are closely related to molecular interactions and spatial arrangements (Figure 10).…”
Section: Film Processing and Device Structural Optimizationmentioning
confidence: 99%
“…Different from powder processing and vacuum evaporation, in which vapor is transported to a substrate to form thin films, due to its simple operation process and low cost, spin-coating is compatible with widely available nanosized CDs that are easily carbonized at high temperatures. [160,161] However, during film processing, the film morphology and microstructure are completely different under different conditions, especially considering that CDs experience molecular rearrangement, aggregation and assembly that are quite different from the dispersed monomolecular structure in solution states. The commonly used processing techniques are still immature for CD materials whose optical properties are closely related to molecular interactions and spatial arrangements (Figure 10).…”
Section: Film Processing and Device Structural Optimizationmentioning
confidence: 99%
“…[32] The long fluorescence lifetime provides much room for improving device stability and luminescent properties. [17,34]…”
Section: Cds Characteristicsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] The former benefits to realizing large-size displays and lighting. The stateof-the-art CDs-based electroluminescent LEDs are assembled using pure CDs emitter [14][15][16][17][18] or CDs-doped guest-host emitting system. [15,[19][20][21][22][23] Fantastic CDsbased LEDs have been rapidly developed after the first report by Ma et al [14] Device luminance with dozens to over a hundred cd m À2 has been demonstrated from pure CDs emitters.…”
Section: Introductionmentioning
confidence: 99%
“…This can be accomplished either via employing CQDs as a single emissive layer or blending them into organic agents like poly(N-vinylcarbazole) (PVK). 13 CQDs usually suffer from quenched luminescence in the solidstate form, 14 resulting in a reduced luminance for CQD-LED. 15 Doping CQDs in poly(N-vinylcarbazole) (PVK) is one way to improve the low luminance of the device to reach a desired blue, green, or red emission or to produce a white emission.…”
Section: Introductionmentioning
confidence: 99%
“…However, the fabrication of an electroluminescent WLED is more demanding and challenging from a technological point of view. This can be accomplished either via employing CQDs as a single emissive layer or blending them into organic agents like poly­( N -vinylcarbazole) (PVK) . CQDs usually suffer from quenched luminescence in the solid-state form, resulting in a reduced luminance for CQD-LED .…”
Section: Introductionmentioning
confidence: 99%